Dreaming, insomnia, and choreographic creativity of young female dancers: a cross-sectional preliminary study - Nishida, Masaki; Goro, Amina (Creativity Studies, 2025)
Human creative activities have been postulated to be related to insomnia and dreaming during sleep. The current preliminary cross-sectional study investigated the associations between insomnia, dreaming, and creativity of choreography in young female dancers. Forty-six female contemporary dancers were included in the present online study and divided into two groups, creative choreographic dancers and non-choreographers, according to their experienced professional roles. The frequency and contents of dreams and nightmares were collected from the participants. In the choreographer group, the frequency of nightmares was significantly correlated with sleep duration and quality among Athens insomnia scale variables. Choreographers also exhibited a significant correlation between the frequency of nightmares and positive thinking tendencies. The non-choreographer group similarly revealed a significant correlation between the frequency of nightmares and Athens insomnia scale variables. The present results suggest that creativity in dance choreography is related to dream frequency, although it is less associated with dream content. Nightmare is less associated with subjective insomnia in creative choreographic dancers than in non-creative dancers, implying the involvement of neuro-psychological mechanisms related to the resilience process. Future research should explore the characteristics of creativity and regular sleep quality and could benefit from including external physiological measures to evaluate sleep propensities.